Induction of variation invitro in sarpagandhi (rauvolfia serpentina L.) - Alok (Department of Plantation Crops and Spices, College of Horticulture, 2009)
A study was conducted at the College of Horticulture, Vellanikkara during the year 2006-2008 to induce variability in four accessions of sarpagandhi (Rauvolfia serpentina L.) through indirect organogenesis and in vitro colchiploidy and to conduct a preliminary evaluation of the variants. Axenic cultures could be established in four accessions of sarpagandhi through enhanced release of axillary buds in MS medium supplemented with 2.0 mg l-1 BA + 0.5 mg l-1 NAA. MS medium supplemented with 0.5 mg l-1 NAA promoted rooting and plantlets established well in potting mixture containing sand, soil, FYM in 1: 1: 1 ratio, enriched with phosphorous solubilizing bacteria + Trichoderma. The four accessions showed variation in morphogenic response with RS 4 showing maximum response. Indirect organogenesis in four accessions was standardised. Nodal segments were identified as the best explant for establishing callus cultures in sarpagandhi. Media combinations with 2,4-D + BA were superior to NAA + BA giving higher callusing percent, callus growth and early callus induction. The best media combination for callus initiation and proliferation was MS medium supplemented with 1.0 mg l-1 2,4-D + 0.2 mg l-1 BA in RS 1 accession and MS medium supplemented with 3.0 mg l-1 2,4-D + 0.5 mg l-1 BA for RS 2 accession. For shoot morphogenesis, MS medium supplemented with 2.0 mg l-1 BA + 0.5 mg l-1 NAA was found ideal in the four accessions. Genotypic differences were noted in morphogenic response of callus cultures. Shoot morphogenesis percentage was maximum in RS 3 whereas proliferation was maximum in RS 4 and morphogenesis was quick in RS 1. Calli clones from two accessions varied greatly from control plants in growth attributes and the study highlighted the possibility of isolating variants with higher alkaloids and ploidy levels. The procedure for in vitro polyploidisation using colchicine was standardised. Nodal explants treated for 1 h with colchicine concentrations of 50 or 100 ppm exhibited maximum variation and vigour in the regenerants. Individual plants among in vitro colchicine treated regenerants with fewer stomata and larger size could be isolated as suspected polyploids.